(3OQI GdZhGU aj GhgGe GdNhGUs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s
(3ChdgG (B:s
(3GeG HYO MeO Gdgd GdPi Ye YHGOg HhXGFa GdYhGQa aEfi QCjJ cKjQkG eef jSehG GSeg GdQJH hJSehG HSeI GdGOH aCdaJ gPG GdcJGH JHUQI def JHUQ hJPcQI def CQGO Gf jPcQhGSejJg OQI GdZhGU ai ChgGe GdNhGU s
(3BNQgG (B:s
(3hef Xf eef jdGbi GdMQhH HCf dGjUGH abO Xf YLRkG hef Gddg GSFdge GdJhajb ddebGd GdeJYdb HGdEUGHI hGdaYGd MSf GdGKGHI s
(3GdfSNI HgG MhGTs
(3HMhGTjgG MhGTi hJbjjOGJs
(3fSNI KGdKI s
(3fSNI fajSI heVHhWI YdjgG JedcGJ dcKjQ ef GdYdeGA hYdjgG JhbjY bWH GdOjf GdMfai hGHf YdGb GdHcQi GdUhjbi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
Keywords: (3GddZIs